Health seeking and access to care for children with suspected dengue in Cambodia: An ethnographic study - Manderson Lenore; Khun Sokrin (BMC, 2007)
Abstract Background The continuing contribution of dengue fever to the hospitalization and deaths in hospital of infants and small children in Cambodia is associated with delays in presentation for medical attention, diagnosis and appropriate care. It is important to identify the reasons that influence these delays, in order to develop appropriate interventions to redress the impact of dengue. Methods Data on health seeking were collected during an ethnographic study conducted in two villages in the eastern province of Kampong Cham, Cambodia in 2004. Interviews were conducted with mothers whose children had been infected with suspected dengue fever, or who had been sick for other reasons, in 2003 and 2004. Results Women selected a therapeutic option based on perceptions of the severity of the child's condition, confidence in the particular modality, service or practitioner, and affordability of the therapy. While they knew what type of health care was required, poverty in combination with limited availability and perceptions of the poor quality of care at village health centers and public referral hospitals deterred them from doing so. Women initially used home remedies, then sought advice from public and private providers, shifting from one sector to another in a pragmatic response to the child's illness. Conclusion The lack of availability of financial resources for poor people and their continuing lack of confidence in the care provided by government centres combine to delay help seeking and inappropriate treatment of children sick with dengue.